The Thrombopoietin Receptor, MPL, Is a Therapeutic Target of Opportunity in the MPN - Spivak, Jerry L.; Moliterno, Alison R. (Frontiers in Oncology, 2021)
The myeloproliferative neoplasms, polycythemia vera, essential thrombocytosis and primary myelofibrosis share driver mutations that either activate the thrombopoietin receptor, MPL, or indirectly activate it through mutations in the gene for JAK2, its cognate tyrosine kinase. Paradoxically, although the myeloproliferative neoplasms are classified as neoplasms because they are clonal hematopoietic stem cell disorders, the mutations affecting MPL or JAK2 are gain-of-function, resulting in increased production of normal erythrocytes, myeloid cells and platelets. Constitutive JAK2 activation provides the basis for the shared clinical features of the myeloproliferative neoplasms. A second molecular abnormality, impaired posttranslational processing of MPL is also shared by these disorders but has not received the recognition it deserves. This abnormality is important because MPL is the only hematopoietic growth factor receptor expressed in hematopoietic stem cells; because MPL is a proto-oncogene; because impaired MPL processing results in chronic elevation of plasma thrombopoietin, and since these diseases involve normal hematopoietic stem cells, they have proven resistant to therapies used in other myeloid neoplasms. We hypothesize that MPL offers a selective therapeutic target in the myeloproliferative neoplasms since impaired MPL processing is unique to the involved stem cells, while MPL is required for hematopoietic stem cell survival and quiescent in their bone marrow niches. In this review, we will discuss myeloproliferative neoplasm hematopoietic stem cell pathophysiology in the context of the behavior of MPL and its ligand thrombopoietin and the ability of thrombopoietin gene deletion to abrogate the disease phenotype in vivo in a JAK2 V617 transgenic mouse model of PV.